La ciudad como museo: Interpretaciones para construir utopía y urbanidad - Roser Calaf; Sué Gutiérrez (Midas: Museus e Estudos Interdisciplinares)
Two cities, Gijón and Barcelona (Spain), represent the idea of city-museum, city-facility, and, potentially, educational city, founded in the city as a construction of urbanity. Both are educational cities, and have generated heritage actions from obsolete industrial environments, introducing artworks, public sculpture, urban design furniture and unique buildings to transform and improve important cultural and social public places. A process of natural heritage education has been carried out at Barcelona, where the symbolism and value of art has been understood as another modern view into the cosmopolitan profile of the city. Gijón required a more direct and education-specific museum intervention, teaching its citizens to discover the true value of the historical and artistic heritage of their streets. An urban symbolism which acts as identitarian project has been created, transmitting cultural identity in both cases.